Empirical relationships between Arias Intensity and peak ground acceleration for western China - Liu, Jia Mei; Zhang, Bin; Zhao, Xu Dong (Frontiers in Earth Science, 2024)
We establish empirical relationships for Arias Intensity (AI) and peak ground acceleration (PGA) for western China, utilizing 3169 horizontal and 979 vertical strong motion records with PGA ≥ 0.01g from 274 earthquakes (M S 4.0-8.0), originating in eight provinces in southwest (Yunnan, Sichuan) and northwest China (Gansu, Shaanxi, Ningxia, Qinghai, Inner Mongolia, and Xinjiang). The influences of M S and epicenter distance are validated. The dependence on V S30 and generic site classes (i.e. rock and soil) is explored. The results confirm that the logarithm of AI increases linearly with the increase of the logarithm of PGA and M S , and decreases with the logarithm of V S30 . However, the influence of site conditions on AI-PAG relationships can't be recognized by the simple generic rock and soil site classes. The epicenter distance has little effect on the AI-PAG relationships. Empirical relationships are developed to estimate horizontal or vertical AI as a function of PGA (basic model), PGA and M S (model 2) for southwest, northwest, and western China, using all the records. Empirical relationships for AI as a function of PGA, M S , and V S30 (model 1) are established using the 2248 horizontal (70.9% of the total) and 670 vertical (68.4% of the total) records with V S30 . The notable disparity between model 1 of the southwest and northwest regions indicates that the AI-PGA correlation is region-dependent. This region-dependent effect is chiefly attributed to local site conditions. We consider our new models to be applicable for M S ranging from 4.0 to 8.0, V S30 between 148 and 841m/ s and PGA ≥ 0.01g. They enable one way of estimating AI from PGA for western China and will also enhance the understanding of AI attenuation.